KEABSAHAN PERJANJIAN ELEKTRONIK DAN PENYELESAIAN SENGKETA WANPRESTASI DEBITUR PINJAMAN ONLINE - Kiswah, Maftuha; Rukaman Wibisono, Wina Febrianti; Setyawan, Fendi; Adonara, Firman Floranta (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
The rapid growth of financial technology (fintech) in the form of peer-to-peer lending has transformed borrowing and lending practices in Indonesia. Electronic contracts serve as the main legal instrument between creditors and debtors, yet they raise issues of validity, consumer protection, and dispute resolution in cases of default. This study employs a normative juridical approach by analyzing Law No. 8 of 1999 on Consumer Protection, Law No. 19 of 2016 on Electronic Information and Transactions, Government Regulation No. 80 of 2019 on Electronic Trade, and Financial Services Authority regulations (POJK No. 61/2020 and SEOJK No. 19/2023). The findings reveal that the validity of electronic contracts is legally recognized as long as they meet the essential requirements of agreement, capacity, lawful cause, and specific object, as stipulated in the Indonesian Civil Code. Disputes arising from debtor defaults can be resolved through litigation, such as simplified lawsuits, or non-litigation mechanisms, including mediation, Alternative Dispute Resolution Institutions (LAPS), and complaint facilities provided by the Financial Services Authority (OJK). However, challenges persist due to consumers’ low legal literacy, unethical debt collection practices, and asymmetry in bargaining positions. Therefore, strengthening the regulatory framework for electronic contracts and implementing fair and accessible dispute resolution mechanisms are necessary to enhance legal certainty and consumer protection. Keywords: Electronic Contract, Online Loan, Default, Consumer Protection, Dispute Resolution.